KAJIAN TEKNOLOGI TEPUNG KASAVA: PROSPEK DAN KENDALA PEMANFAATAN UNTUK INDUSTRI PANGAN BERBASIS TEPUNG - Widowati, Sri (Jurnal Ilmiah Pangan Halal, 2020)
Various local carbohydrate sources can be produced into flour to substitute for flour, save foreign exchange and improve food security. Based on the availability of raw materials and prices, cassava has the most potential to be processed into flour. The research results of cassava are also the most abundant among the carbohydrate source commodities. The name cassava has an inferior stigma in society, compared to rice and wheat, even corn. This is one of the considerations that cassava flour is then better known as cassava flour, to improve the image and interest of users. Cassava flour, with various technological variants, and other local flours have been widely researched, produced and used for various flour-based food products, but nationally the real impact on decreasing wheat consumption is still not significant. Therefore, this paper discusses the prospects and constraints of its use in the food industry. Keywords: Food Security, Carbohydrate Source, Casava Flour.